Gambaran Tingkat Kualitas Hidup pada Usia Produktif dengan Kelebihan Berat Badan di Kota Palu - Muhamad Rinaldhi Tandah; Almira Azahriantika; Afriani Kusumawati; Khusnul Diana (Jurnal Farmasi Indonesia, 2024)
Quality of life is a self-view of an individual in the aspect of assessing one's life. Being overweight to obese of productive age is a factor that can influence the level of assessment of the quality of life. The purpose of this study was to determine the picture of the level of quality of life at a productive age with overweight using pharmacological and non-pharmacological therapies, and to find out whether there was a significant difference between the level of quality of life and overweight using pharmacological and non-pharmacological therapies. This study used a non-experimental method that is descriptive with cross-sectional data collection. Respondent data will be retrieved using a questionnaire (WHOQOL-BREF) and will be analyzed using t-test. The determination of samples in this study using the Yamane and Isaac formulas from a total population of 649 people obtained a sample of 155 respondents. The results of this study can interpret from the data of respondents who use pharmacological therapy, the highest average score is found in the psychological with a value of 71.65, where these results in general in the good category. The highest average score with non-pharmacological therapy is 75.7 with a good category. The significance value obtained from the Independent sample t-test was 0.75 which can interpret that this data did not have a significant difference, due to factors of therapy consumed by respondents by combining pharmacological therapy with the use of other medicines such as herbal medicine or traditional medicine, and supported by a poor lifestyle.